(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2024)
India has a large number of ethnomedicinal plants growing under different geographical conditions. The article emphasizes on think locally and act globally scenario of the hidden Indian medicinal knowledge and its worldwide implementation as life saving novel herbal formulations. The article also emphasizes possible role of novel herbal formulations based on ethnomedicinal knowledge in uplifting of Indian economy. Looking into the current situation of biopiracy and gene robbing, the country should take immediate steps to bioprospect its ethnomedicinal knowledge and to commercialize novel herbal formulations at global level.